1956
DOI: 10.1021/jf60066a004
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides in Animal Feeds, Effects of Feeding Dieldrin- and Heptachlor-Treated Alfalfa Hay to Dairy Cows

Abstract: Eight dairy cows were fed alfalfa hay treated with either heptachlor or dieldrin and feeding trials were conducted for 112 days, during which milk samples were taken weekly. A small amount of dieldrin was found in the milk and a considerable amount in the butter from cows fed hay treated with 1 and 4 ounces of dieldrin per acre. No heptachlor was excreted in the milk. Heptachlor epoxide was found in milk and butter from cows fed hay treated with 4 ounces of heptachlor per acre. There was no detectable effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1958
1958
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…material by the animal's body metabolism. Such a conversion has been noted in the case of heptachlor, where an epoxide analog has been found deposited in the fat (8) and secreted in the milk (5) of animals ingesting heptachlor. This was confirmed by Ely et al ( 7), using a similar heptachlor intake level.…”
Section: Resultsmentioning
confidence: 82%
“…material by the animal's body metabolism. Such a conversion has been noted in the case of heptachlor, where an epoxide analog has been found deposited in the fat (8) and secreted in the milk (5) of animals ingesting heptachlor. This was confirmed by Ely et al ( 7), using a similar heptachlor intake level.…”
Section: Resultsmentioning
confidence: 82%
“…residues, respectively, in their milk. HARRIS et al (1956) found 0.4 and 1.7 p.p.m. residues in milk of cows fed alfalfa hay treated with one and four oz./acre of dieldrin for 112 days.…”
Section: C) Dieldrinmentioning
confidence: 93%
“…Dairy cows were fed hay from a meadow treated with heptachlor at 1 or 4 ounces per acre, corresponding to approximately 0.06 and 0.22 mg/kg of heptachlor residue in the hay for 112 days (Harris et al, 1956). The concentration of heptachlor in hay and the amount given resulted in an intake of approximately 0.002 and 0.007 mg/kg b.w per day.…”
Section: Ruminantsmentioning
confidence: 99%